2007
DOI: 10.4319/lo.2007.52.5.1824
|View full text |Cite
|
Sign up to set email alerts
|

Sources and sinks of methane in Lake Baikal: A synthesis of measurements and modeling

Abstract: We studied the methane (CH 4 ) budget of Lake Baikal, the most voluminous lake in the world and the only freshwater body with known occurrences of methane hydrates in the sediments. CH 4 concentrations were measured in water samples taken during six expeditions between October 2002 and June 2004; these expeditions covered the entire lake volume. A one-dimensional model was applied to (1) estimate the large-scale vertical CH 4 fluxes within the South Basin of Lake Baikal, (2) determine the exchange with the atm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 54 publications
4
31
0
4
Order By: Relevance
“…Process-based models have been developed for the fate of organic carbon in lakes (Hanson et al 2004), the release of methane bubbles from lake sediments (Makhov and Bazhin 1999), the dissolution of methane during the rise of the bubbles through the water column (McGinnis et al 2006), and gas exchange between the lake surface and the atmosphere (Guérin et al 2007). A 1-D reaction-transport model has been applied to the Lake Baikal methane balance (Schmid et al 2007). Whole lake and reservoir GHG flux modeling approaches have included the development of regression models (Bastviken et al 2004) and methane budgets (Bastviken et al 2008), as well as dynamical numeric approaches (Abril et al 2005;Thérien and Morrison 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Process-based models have been developed for the fate of organic carbon in lakes (Hanson et al 2004), the release of methane bubbles from lake sediments (Makhov and Bazhin 1999), the dissolution of methane during the rise of the bubbles through the water column (McGinnis et al 2006), and gas exchange between the lake surface and the atmosphere (Guérin et al 2007). A 1-D reaction-transport model has been applied to the Lake Baikal methane balance (Schmid et al 2007). Whole lake and reservoir GHG flux modeling approaches have included the development of regression models (Bastviken et al 2004) and methane budgets (Bastviken et al 2008), as well as dynamical numeric approaches (Abril et al 2005;Thérien and Morrison 2005).…”
Section: Resultsmentioning
confidence: 99%
“…As a result of increased stability of the metalimnion below the surface mixed layer (Schmid et al 2007), vertical mixing decreases during the summer period. Major factors influencing vertical exchange processes during summer stratification can include vertical movements of water masses within cyclonic currents driven by the winds (Shimaraev and Ladeyshchikov 1986) as well as horizontal heterogeneity of water temperature and density.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption certainly holds for small, shallow ecosystems where the surface layers are in relatively close contact with sediments. Yet CH 4 supersaturation is also prevalent in large, deep lakes 3,5,[7][8][9][10][11][12] and oceanic surface waters [13][14][15][16][17] , where deeper water columns result in significantly reduced surface water exchange with anoxic sediments. Studies of CH 4 dynamics in surface waters of oceans and large lakes have indeed concluded that pelagic CH 4 supersaturation cannot be sustained either by lateral inputs from the littoral or from benthic inputs alone 9,10,[13][14][15][17][18][19] .…”
mentioning
confidence: 99%